Phase Angle as a Biomarker for Frailty and Postoperative Mortality: The BICS Study - Louis Mullie; Alexandrine Obrand; Melissa Bendayan; Amanda Trnkus; Marie‐Claude Ouimet; Emmanuel Moss; Annabel Chen‐Tournoux; Lawrence G. Rudski; Jonathan Afilalo (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2018)
Background Phase angle (PA) is a bioimpedance measurement that is determined lean body mass and hydration status. Patients with low PA values are more likely to be frail, sarcopenic, or malnourished. Previous work has shown that low PA predicts adverse outcomes after cardiac surgery, but the effect of PA on survival has not previously been assessed in this setting. Methods and Results The BICS (Bioimpedance in Cardiac Surgery) study recruited 277 patients undergoing major cardiac surgery at 2 university‐affiliated hospitals in Montreal, QC, Canada. Bioimpedance measurements as well as frailty and nutritional assessments were performed preoperatively. The primary outcome was all‐cause mortality. Secondary outcomes were 30‐day mortality, postoperative morbidity, and hospital length of stay. There were 10 deaths at 1 month of follow‐up and 16 deaths at 12 months of follow‐up. PA was associated with age, sex, body mass index, comorbidities, and frailty, as measured by the Short Physical Performance Battery and Fried scales. After adjusting for Society of Thoracic Surgeons–predicted mortality, lower PA was associated with higher mortality at 1 month (adjusted odds ratio, 3.57 per 1° decrease in PA; 95% confidence interval, 1.35–9.47) and at 12 months (adjusted odds ratio, 3.03 per 1° decrease in PA; 95% confidence interval, 1.30–7.09), a higher risk of overall morbidity (adjusted hazard ratio, 2.51 per 1° decrease in PA; 95% confidence interval, 1.32–4.75), and a longer hospital length of stay (adjusted β, 4.8 days per 1° decrease in PA; 95% confidence interval, 1.3–8.2 days). Conclusions Low PA is associated with frailty and is predictive of mortality, morbidity, and length of stay after major cardiac surgery. Further work is needed to determine the responsiveness of PA to interventions aimed at reversing frailty.